ERASING OR RESTORING UKRAINIAN HERITAGE - Fabien Bellat (Docomomo Journal, 2022)
In Ukraine, heritage has been a battlefield since World War II. In those years, the Kyiv reconstruction was dominated by Russian architects, and Ukrainian architects were marginalized in their own city. However, restoration of churches slowly became a topic where policy changed from Stalin’s doctrines to his successors’ principles, and where Ukrainian builders managed to gain some success in heritage protection. This prevailed more after independence in 1991. The present war that Putin triggered against Ukraine is accelerating heritage issues. The destructions of this war have hit all types of buildings, but some of the reactions of the people in charge should arouse worry for the preservation of the 20th century heritage. The obvious lack of interest for the modern heritage of the 1920s and 1930s, or even for the more classical Stalinist buildings of the 1940s and 1950s, expresses a kind of selective memory. Soon this may lead to regrettable deletions, adding more disaster to the destructive traces that the war has already left. Consequently, and despite the many ghosts left by the Soviet regime (something which understandably led to the controversial decommunization laws), more studies should be launched on the Constructivist and Stalinist legacy in particular, in order to help saving this significant part of Ukraine history. This research could be useful when the reconstruction and conservation of the damaged towns eventually begins.